Tailoring selective pores of carbon molecular sieve membranes towards enhanced N-2/CH4 separation efficiency - Yu, Hyun Jung; Shin, Ju Ho; Lee, Albert S.; Hwang, Seung Sang; Kim, Jeong-Hoon; Back, Seoin; Lee, Jong Suk (ELSEVIER, 2021)
Membrane-based separation technology is attractive for upgrading small-scale natural gas due to the benefits of the pressure-driven process with a small footprint. Very few carbon molecular sieve (CMS) membranes with high N-2/CH4 separation efficiency have been reported since the relationship between CMS structure and separation performance has not been fully elucidated. Here, we report the significance of controlling the effective pore size in our newly developed hybrid CMS matrix for enhanced N-2/CH4 selectivity based on experimental characterizations and density functional theory (DFT) calculations. A new class of CMS membranes with an excellent N-2/CH4 selectivity is demonstrated by pyrolysis of a homogeneous, hydrogen-bonded blend of BTDA-Durene:DABA (3:2) polyimide and ladder-structured poly(phenyl-co-3-(2-aminoethylamino)propyl)silsesquioxane (LPDA64). DFT calculations suggest that electron accumulation at SiOx phases of hybrid CMS membranes strongly hinders the diffusion of CH4 compared to N-2 due to a larger electron overlap, resulting in a smaller effective pore size. Moreover, elevating the pyrolysis temperatures enhanced the N-2/CH4 solubility selectivity due to the strong repulsive interaction between the newly formed ultramicropores with CH4. As a result, the hybrid CMS membranes showed an excellent single gas and N-2/CH4/C2H6 (20/76/4) mixed gas N-2/CH4 selectivity (28 and 16, respectively).
Keywords: GAS SEPARATION; HYDROGEN SEPARATION; SAPO-34 MEMBRANES; PERFORMANCE; CO2/CH4